Institutional Trust 2009 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Sifo (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by TNS Sifo and involved 1000 individuals who answered a web survey between October 17 and November 2, 2009. The survey comprised 33 institutions/companies/media companies and political parties. The 2009 survey also included questions about the media coverage of the coalition government, the opposition, and the Swedish EU presidency. In addition, there were questions on Internet use and the Internet as a tool for democracy.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2009 genomfördes av TNS Sifo och omfattade 1000 personer som besvarade en nätenkät. Studien genomfördes 17/10 - 2/11 2009 och innefattade 33 institutioner/företag/medier/partier. I 2009 års undersökning ingick även frågor om massmediernas rapportering om Alliansregeringen, oppositionen och det svenska ordförandeskapet i EU. Dessutom ingår frågor om Internetanvändning och bedömningar av Internet som ett instrument för demokrati.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2009
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper